Tackling Nurse Shortages in OECD Countries - Simoens, Steven (OECD Health Working Papers, 2005)
There are reports of current nurse shortages in all but a few OECD countries. With further increases in demand for nurses expected and nurse workforce ageing predicted to reduce the supply of nurses, shortages are likely to persist or even increase in the future, unless action is taken to increase flows into and reduce flows out of the workforce or to raise the productivity of nurses. This paper analyses shortages of nurses in OECD countries. It defines and describes evidence on current nurse shortages, and analyses international variability in nurse employment. Additionally, a number of demand and supply factors that are likely to influence the existence and extent of any future nurse shortages are examined. In order to resolve nurse shortages, the paper compares and evaluates policy levers that decision makers can use to increase flows of nurses into the workforce, reduce flows out of the workforce, and improve nurse retention rates. Although delayed market response may have been ...